A carborane-triggered metastable charge transfer state leading to spontaneous recovery of mechanochromic luminescence. Issue 84 (5th October 2016) - Tu, Deshuang; Leong, Pakkin; Li, Zhihong; Hu, Rongrong; Shi, Chao; Zhang, Kenneth Yin; Yan, Hong; Zhao, Qiang
Abstract : Spontaneous recovery of mechanochromic luminescence was realized by carborane-functionalized anthracene derivatives. Abstract : An efficient strategy was designed to realize spontaneous recovery of mechanochromic luminescence by carborane-functionalized anthracene derivatives. A metastable charge-transfer emission from anthracene to o -carborane is responsible for this process.